Efektifitas Komunikasi InaRisk Personal Membangun Budaya Sadar Bencana Masyarakat - Lomban, Ario Akbar; Ariyani, Nafiah (HK-Publishing, 2023)
AbstractIn the human life, humans will always face risks and hazards. Hazards can emerge from natural factors, human factors and technology. Hazards will become disaster risks, if they threaten human vulnerability. The constitution number 24 of 2007 concerning disaster management exists as an effort to reduce disaster risk from the geographical location of Indonesia's territory which is prone to geological, hydrometeorological, biological, technological, health and environmental degradation. Hazard as a trigger can transform into a disaster when the high vulnerability and low capacity meet causing an inability to respond the hazards. This inability can also be interpreted by understanding disaster knowledge. Hazard and risk potentials are something that can be predicted in a situation full of uncertainty and decisions that need to be taken either by individuals or organizations. In the context of disaster knowledge, InaRisk Personal is risk communication as an effort to convey messages about changing people's mindsets and behavior to manage potential disaster hazards for safety. InaRisk Personal is a mobile based information system prepared by the National Disaster Management Authority (BNPB) that displays disaster risk levels and recommendations for community safety actions in the pre-disaster, during and post-disaster. The qualitative method with literature study approach is used to explore and understand the considered meaning of social or humanitarian issues from an individual or a group of individuals (Cresswell, 2009) to describe BNPB's communication strategy in marketing the InaRisk Personal platform as an information system for preparedness community in facing disasters.Keywords: Disaster Risk, Risk Communication, System Information, Communication StrategyÂ AbstrakKehidupan manusia selalu berhadapan dengan risiko dan bahaya. Bahaya dapat timbul karena faktor alam, manusia dan teknologi. Bahaya (hazards) akan menjadi risiko bencana (disaster risk), manakala mengancam variable kerentanan (vulnerability) manusia. Undang-Undang Nomor 24 Tahun 2007 tentang Penanggulangan Bencana hadir sebagai upaya Pengurangan Risiko Bencana dari letak geografis wilayah Indonesia yang rawan bencana geologi, hidrometeorologi, biologi, teknologi, kesehatan dan penurunan kualitas lingkungan. Bahaya sebagai pemicu dapat berpotensi menjadi bencana, ketika faktor kerentanan tinggi masyarakat dan kapasitas (capacity) rendah bertemu menyebabkan ketidakmampuan merespon bahaya. Ketidakmampuan itu dapat diartikan terbatasnya pengetahuan kebencanaan. Bahaya dan risiko adalah sesuatu yang dapat diprediksi dalam situasi yang penuh dengan ketidakpastian dan perlu mengambil keputusan cepat dan tepat oleh individu ataupun organisasi. Dalam konteks kebencanaan, InaRisk Personal merupakan komunikasi risiko sebagai upaya menyampaikan pesan perubahan pola pikir dan perilaku masyarakat menyikapi potensi bahaya bencana untuk keselamatan. InaRisk Personal adalah sistem informasi berbasis mobile yang menampilkan tingkat risiko bencana dan rekomendasi keselamatan masyarakat pada fase prabencana, saat maupun pascabencana. Metode kualitatif dengan pendekatan studi literatur untuk mengeksplorasi dan memahami makna yang dipertimbangkan dari masalah social dari individu atau sekelompok individu (Cresswell, 2009) untuk menggambarkan strategi komunikasi BNPB dalam memasarkan platform InaRisk Personal sebagai sistem informasi untuk kesiapsiagaan masyarakatÂ menghadapi bencana.Kata Kunci: Risiko Bencana, Komunikasi Risiko, Sistem Informasi, Strategi Komunikasi